Constitucionalismo, imprensa e opinião pública nas monarquias dos Bragança: Portugal e Brasil (1826-1834) - Raphael Rocha de Almeida (2019)
This thesis analyzes two simultaneous and interrelated movements. Firstly, attention is paid to the struggles around liberal constitutionalism in Portugal and Brazil, a process marked by interfaces and connections. Afterward, it is dedicated to analyzing the uses of print and the transit of news (printed, handwritten and oral), as well as people (news spokespersons and discussion-makers) from Brazil to Portugal and vice versa, during the period running from 1826 to 1834 within a communication circuit of transnational amplitude. The milestones coincide with the death of D. João VI in 1826, an event that started the succession dispute in Portugal, extending until 1834, the year of the victory of the liberal forces and the death of D. Pedro I. Although restricted to the political context circumscribed to the two deaths – D. João VI and D. Pedro's – when necessary, the analysis goes back to earlier periods and extends beyond 1834.The assumption is that, even after Independence, the links between the histories of Portugal and Brazil inevitably remained strong and support the hypothesis that the respective public spheres of political discussion – territorially delimited – affected each other mutually because it was inserted in a communication circuit of a transnational character. In these public spheres, political projects were publicized to a community of readers that went beyond the respective boundaries of the constitutional States in formation, highlighting the transnational dimension of the debate processed in this context.